Dynamic analysis of 22 serum biomarkers following pneumothorax - Jirui Chen; Qiang Lyu; Cheng Wang; Qianyu Han; Yuanyuan Wang; Mingwei Jiang; Lei Xue; Yuxiang Jin (Frontiers in Medicine, 2026)
Background Pneumothorax is a common respiratory emergency. Current diagnosis primarily relies on imaging examinations, but these have insufficient sensitivity for early or occult cases, and there is a lack of highly specific molecular markers. Investigating the dynamic changes in serum biomarkers is of great significance for the early diagnosis and intervention of pneumothorax. Methods A rat pneumothorax model was established. Serum was collected before modeling and at 1, 2, 6, 12, 24, and 48 h after modeling. Using pre-modeling rat serum marker levels as a baseline, 22 biomarkers (including inflammatory factors, fibrosis-related molecules, immunomodulatory molecules, and metabolic indicators) were detected using enzyme-linked immunosorbent assay (ELISA). Small animal ultrasound was used to verify model establishment. Results The rat pneumothorax model was successfully established, with ultrasound showing the loss of the lung sliding sign. The biomarkers exhibited four dynamic patterns: (1) Early rapid increase in pro-inflammatory factors (tumor necrosis factor- α , interleukin-1 β , etc.); (2) Sustained or fluctuating increase in fibrosis-related molecules (transforming growth factor-β, collagen, etc.); (3) Sustained decrease in the anti-inflammatory factor interleukin-10; (4) Fluctuating changes in metabolic indicators and aquaporin markers (25-hydroxyvitamin D, aquaporin-4/5). Notably, to our knowledge, this study is the first to discover early, significant, and rapid increases in tartrate-resistant acid phosphatase (TRACP), intercellular adhesion molecule-1 (ICAM-1), and nuclear factor-κB (NF-κB) in a pneumothorax model, which may provide a basis for the early diagnosis of pneumothorax. Conclusion This study systematically delineates the dynamic evolution patterns of multiple classes of serum biomarkers following pneumothorax. The novel finding of abnormal elevations in TRACP, ICAM-1, and NF-κB challenges traditional understanding of their functions and provides new potential candidate targets for the early diagnosis of pneumothorax.